2022
DOI: 10.1038/s41598-022-26335-3
|View full text |Cite
|
Sign up to set email alerts
|

Mucus-derived exosome-like vesicles from the Spanish slug (Arion vulgaris): taking advantage of invasive pest species in biotechnology

Abstract: The slug Arion vulgaris has attracted major attention as one of the worst invasive herbivore pests in Europe and is renowned for the stiff mucus it secretes for locomotion. In this study we focused on the isolation and characterisation of extracellular vesicles, specifically exosomes and exosome-like vesicles, from Arion secretions. We developed a method for slug mucus collection and subsequent vesicle isolation by ultracentrifugation. The isolated vesicles with an average diameter of ~ 100 nm carry abundant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…59 Additionally, extracellular vesicles derived from Arion vulgaris mucus were successfully loaded with the chemotherapy drug doxorubicin. Using in vitro internalization assays, it was demonstrated that these vesicles can penetrate human glioblastoma cells, 60 highlighting opportunities for targeted cancer therapy.…”
Section: Multifunctional Biomaterials With Diverse Biomedical and Cos...mentioning
confidence: 99%
See 2 more Smart Citations
“…59 Additionally, extracellular vesicles derived from Arion vulgaris mucus were successfully loaded with the chemotherapy drug doxorubicin. Using in vitro internalization assays, it was demonstrated that these vesicles can penetrate human glioblastoma cells, 60 highlighting opportunities for targeted cancer therapy.…”
Section: Multifunctional Biomaterials With Diverse Biomedical and Cos...mentioning
confidence: 99%
“…These findings open up intriguing possibilities for their use in pest management strategies and broader applications within the field of plant biotechnology. 60 Realizing the promising biotechnological potential of gastropod mucus requires moving beyond speculative possibilities to critically evaluate its technical viability based on current research. For instance, developing mucus-based medical adhesives demands greater detail on methods for the isolation and engineering of adhesive proteins like those studied in Arion subf uscus 6 and marsh periwinkle mucus.…”
Section: Potential Applications Of Gastropod Mucus In Biotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative sequencing suggested involvement in shell pigmentation. Mucus from the invasive slug Arion vulgaris contained abundant EVs, which could be internalised by plant and human cells and loaded with chemotherapy agents ( Liegertová et al, 2022 ).…”
Section: Molluscsmentioning
confidence: 99%